An integrated approach for identification and characterization of palaeo-exposure surfaces in the upper Sarvak Formation of Abadan Plain, SW Iran. (September 2018) - Assadi, Ali; Honarmand, Javad; Moallemi, Seyed Ali; Abdollahie-Fard, Iraj
Abstract: Palaeo-exposure surfaces are common geologic features in the Cretaceous sedimentary record of the Middle East. Two important disconformity surfaces have influenced the Cenomanian-Turonian intervals of the Sarvak Formation in the Abadan Plain. These surfaces had substantial controls on reservoir quality of their underlying succession. In this study obtained data from macroscopic core descriptions, microscopic petrography, geochemical analysis, spectral gamma ray log signatures, and clay minerals frequency in three hydrocarbon fields are combined and used for interpretations. Dissolution, cementation and recrystallization are the main diagenetic features related to the disconformity surfaces. Intensity and development of these diagenetic alterations are highly dependent on depositional facies characteristics of the underlying sequences. In mud-dominated facies, the main diagenetic process is recrystallization, while the grain-dominated facies were highly subjected by dissolution and cementation. Based on the geochemical analysis, there is an increase in Al2 O3, SiO2, Fe2 O3, Al, Fe, Mn, and Rb content beneath the disconformities. In contrast, the Sr concentration displays a decreasing trend towards the disconformities. On spectral gamma ray logs, depletion of the uranium and high values of CGR/SGR and TH/U ratios are attributed to the meteoric diagenesis. In addition, obtained data from SEM and XRD analysis indicate that the montmorillonite is the most abundant clay mineral in uppermost part of the Sarvak Formation. It shows the highest concentration at the disconformity surfaces which can be quoted to the impact of meteoric diagenesis and development of palaeo-soil horizons. These results are used for reconstruction of diagenetic sequence of the upper Sarvak Formation in subsurface sections of the Abadan Plain. Graphical abstract: Image 1 Highlights: Recognition of palaeo-exposure surfaces of the Sarvak Formation. Distribution of diagenetic products, shows relationship with sedimentary facies. The Cenomanian-Turonian disconformity not confirmed in the global cycle chart. Geochemical data can be used in the assessment of disconformity surfaces.